Rural-urban differences on the rates and factors associated with early initiation of breastfeeding in Nigeria: Further analysis of the Nigeria demographic and health survey, 2013 - Adewuyi, E.; Zhao, Yun; Khanal, V.; Auta, A.; Bulndi, L. (BioMed Central, 2017)
© 2017 The Author(s). Background: This study investigates and compares the rates and factors associated with early initiation of breastfeeding (EIBF) within one hour of birth in rural and urban Nigeria. Methods: Data from the 2013 Nigeria Demographic and Health Survey (NDHS) were analyzed. The rates of EIBF were reported using frequency tabulation. Associated factors were examined using Chi-Square test and further assessed on multivariable logistic regression analysis. Results: The rates of EIBF were 30.8% (95% confidence interval [CI] 29.0, 32.6) and 41.9% (95% CI 39.6, 44.3) in rural and urban residences, respectively (p < 0.001). The North-Central region had the highest EIBF rates both in rural (43.5%) and urban (63.5%) residences. Greater odds of EIBF in rural residence were significantly associated with higher birth order (Adjusted Odds Ratio [AOR] 1.29, 95% CI 1.10, 1.60), large birth size (AOR 1.33, 95% CI 1.10, 1.60), and health facility delivery (AOR 1.46, 95% CI 1.23, 1.72). Rural mothers in the rich wealth index, not working and whose husbands obtained at least a secondary school education had significantly higher odds of early initiation of breastfeeding. Regardless of residence, greater odds of EIBF were significantly associated with non-cesarean delivery (Rural AOR 3.50, 95% CI 1.84, 6.62; Urban AOR 2.48, 95% CI 1.60, 3.80) and living in North-Central (Rural AOR 1.84, 95% CI 1.34, 2.52; Urban AOR 4.40, 95% CI 3.15, 6.15) region. Also, higher odds of EIBF were significantly associated with living in North-East (Rural AOR 1.48, 95% CI 1.05, 2.08; Urban AOR 3.50, 95% CI 2.55, 4.83), South-South (Rural AOR 1.51, 95% CI 1.11, 2.10; Urban AOR 2.84, 95% CI 2.03, 3.97) and North-West (Urban residence only AOR 2.08, 95% CI 1.54, 2.80) regions. Conclusions: Rural-urban differences in the rates and factors associated with EIBF exist in Nigeria with rural residence having significantly lower rates. Intervention efforts which address the risk factors identified in this study may contribute to improved EIBF rates. Efforts need to prioritize rural mothers generally, (particularly, those in rural North-West region) as well as mothers in urban South-West region of Nigeria.